Colossian and Philemon studies : lessons in faith and holiness - Moule, H. C. G., (Handley Carr Glyn), 1841-1920. (London, UK : Pickering and Inglis)
Includes bibliographical references.
Keywords: Bible. -- commentaries; Bible. -- commentaries